Impact of immersive learning environments on the development of technological competencies in students - Mamani-Choque, Marily Yenifer; Machaca-Casani, Javier Ignacio; Maraza-Quispe, Benjamín (International Journal of Evaluation and Research in Education (IJERE), 2025)
This research identifies the need to enhance students’ technological competencies in designing and building technological solutions through immersive learning environments. The study proposes the use of immersive technologies, such as virtual and augmented reality (AR), to foster creativity and improve students’ ability to develop effective solutions. The aim was to evaluate the impact of immersive learning on the competence of “designing and building technological solutions” in higher education students, focusing on four specific capacities: determining, designing, implementing, and validating solutions, as well as promoting innovation. Using a quantitative, descriptive cross-sectional experimental design, structured questionnaires were administered to 35 students engaged in an immersive technology program. Data were analyzed using descriptive and comparative techniques, revealing a significant positive impact on technological competencies. Students found these experiences to be relevant, engaging, and conducive to creativity, improving their ability to design and test solutions. However, challenges such as resource availability and the need for continuous teacher training were noted. The study concludes that immersive technologies are effective in enhancing academic performance and practical skills, emphasizing their integration in various educational contexts to strengthen key competencies essential for the 21st century.